2013
DOI: 10.1038/nchembio.1316
|View full text |Cite
|
Sign up to set email alerts
|

NO-inducible nitrosothionein mediates NO removal in tandem with thioredoxin

Abstract: Nitric oxide (NO) is a toxic reactive nitrogen species that induces microbial adaption mechanisms. Screening a genomic DNA library identified a new gene, ntpA, that conferred growth tolerance upon Aspergillus nidulans against exogenous NO. The gene encoded a cysteine-rich 23-amino-acid peptide that reacted with NO and S-nitrosoglutathione to generate an S-nitrosated peptide. Disrupting ntpA increased amounts of cellular S-nitrosothiol and NO susceptibility. Thioredoxin and its reductase denitrosated the S-nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…The chemistry of thiols (-SH) and NO is established, and their reactions under physiological conditions generates S -nitrosothiols (-SNO). This is also true for the iNT peptide, and thiols of the six cysteine residues are stoichemetrically converted to S -nitrosothiols in vitro (Zhou et al 2013 ). Studies using the gene disruptant and a strain that produces an excess of iNT found a negative correlation between cellular iNT levels and the amount of S -nitrosated proteins, indicating that iNT protects cellular protein thiols from S -nitrosation by scavenging NO under RNS stress.…”
Section: Nitrosothioneinmentioning
confidence: 85%
See 3 more Smart Citations
“…The chemistry of thiols (-SH) and NO is established, and their reactions under physiological conditions generates S -nitrosothiols (-SNO). This is also true for the iNT peptide, and thiols of the six cysteine residues are stoichemetrically converted to S -nitrosothiols in vitro (Zhou et al 2013 ). Studies using the gene disruptant and a strain that produces an excess of iNT found a negative correlation between cellular iNT levels and the amount of S -nitrosated proteins, indicating that iNT protects cellular protein thiols from S -nitrosation by scavenging NO under RNS stress.…”
Section: Nitrosothioneinmentioning
confidence: 85%
“…The yeast GSH-GSNOR system and Fhb constitute a control mechanism of NO that eliminates stress imposed by RNS (Liu et al 2001 ). The recent fi ndings of Fhb in A. oryzae and A. nidulans (Zhou et al 2013 ) indicate that these fi lamentous fungi have NO-detoxifying functions. However, the functions of the GSH/GSNOR system and other proteins in the responses of fi lamentous fungi to NO remain unknown.…”
Section: Stress Imposed By Reactive Nitrogen Species and Responses Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, deletion of this gene results in hypersensitivity to NO and a moderate attenuation of virulence (Hromatka et al, 2005). Other proteins involved in the detoxification of NO are the porphobilinogen deaminase hemC , which promotes the activity of flavohemoglobin, the NO-inducible nitrosothionein ntpA , which scavenges NO through S-nitrosylation in A. nidulans (Zhou et al, 2012, 2013) and S-nitrosoglutathione (GSNO) reductase, which reduces GSNO to ammonia and glutathione disulfide and is important for the detoxification of RNS in C. neoformans (Fernández et al, 2003) and A. fumigatus (Lapp et al, 2014). …”
Section: Attackmentioning
confidence: 99%